Update on histone deacetylase inhibitors in peripheral T-cell lymphoma (PTCL) - Guang Lu; Shikai Jin; Suwen Lin; Yuping Gong; Liwen Zhang; Jingwen Yang; Weiwei Mou; Jun Du (Clinical Epigenetics, 2023)
Abstract Peripheral T-cell lymphomas (PTCLs) are a group of highly aggressive malignancies with generally poor prognoses, and the first-line chemotherapy of PTCL has limited efficacy. Currently, several novel targeted agents, including histone deacetylase inhibitors (HDACis), have been investigated to improve the therapeutic outcome of PTCLs. Several HDACis, such as romidepsin, belinostat, and chidamide, have demonstrated favorable clinical efficacy and safety in PTCLs. More novel HDACis and new combination therapies are undergoing preclinical or clinical trials. Mutation analysis based on next-generation sequencing may advance our understanding of the correlation between epigenetic mutation profiles and relevant targeted therapies. Multitargeted HDACis and HDACi-based prodrugs hold promising futures and offer further directions for drug design.